Secure and Trustworthy Service Composition The Aniketos Approach - Brucker, Achim; Dalpiaz, Fabiano; Giorgini, Paolo; Meland, Per Håkon; Rios, Erkuden (Security and Cryptology, 2014)
The Future Internet envisions a move toward widespread use of services as a way of networked interaction. However, while the technologies for developing and deploying services are well established, methods for ensuring trust and security are fewer and less mature. Lack of trust and confidence in composed services and in their constituent parts is reckoned to be one of the significant factors limiting widespread uptake of service-oriented computing. This state-of-the-art survey illustrates the results of the Aniketos - Secure and Trustworthy Composite Services - project (funded under the EU 7th Research Framework Programme). The papers included in the book describe the solutions developed during the 4-year project to establish and maintain trustworthiness and secure behavior in a constantly changing service environment. They provide service developers and providers with a secure service development framework that includes methods, tools, and security services supporting the design-time creation and run-time composition of secure dynamic services, where both the services and the threats are evolving. The 16 chapters are organized in the following thematic sections: state of the art of secure and trustworthy composite services; the Aniketos platform; design-time support framework; run-time support framework; and case studies and evaluation.